VDC_100102370977.0X000001. Issue 5 (May 2018) - Nahmias, Jeffry; Doben, Andrew; Debusk, George; Winston, Sue; Alouidor, Reginald; Kaye, Thomas; Patterson, Lisa; Garb, Jane; Gross, Ronald
In 2010, 2.5 million people sustained a traumatic brain injury (TBI), with an estimated 75 per cent being mild TBI. Mild TBI is defined as a Glasgow Coma Scale (GCS) of 13 to 15. Based on recent data and our institutional experience, we hypothesized that mild TBI patients, including patients on aspirin, could be safely managed by trauma surgeons without neurosurgical consultation. Trauma patients admitted to a single Level I trauma center from June 2014 through July 2015 aged 18 years or older were evaluated. Patients with a GCS ≥14, regardless of intoxication, with an epidural or subdural hematoma ≤4 mm, trace or small subarachnoid hemorrhage, and/or non-displaced skull fracture were prospectively enrolled. The primary outcomes were needed for neurosurgical consultation and intervention. Secondary outcomes included readmission rate and neurologic morbidity and mortality rate. Of 1341 trauma admits, 77 were enrolled. No patients required neurosurgical intervention. Only 1/75 (1.3%) patients required neurosurgical consultation. Outpatient follow-up was achieved with 75/77 (97.4%) patients. No mortalities, major neurologic morbidities, or readmissions were observed (95% confidence interval 0–4%). None of the 21 patients on aspirin required neurosurgical intervention and only 1/21 (4.8%) patients required neurosurgical consultation with no mortalities observed at follow-up. Management of mild TBI can be safely accomplished by trauma surgeons without routine neurosurgical consultation. Larger multicenter prospective studies are required to evaluate our finding that this also may be safe in patients taking aspirin.